Acute Seroconversion of Eastern Equine Encephalitis Coinfection With California Serogroup Encephalitis Virus - Cho, Jonathan J.; Wong, Joshua K.; Henkel, Jacqueline; DeJesus, Reordan O.; Nazario-Lopez, Bernadette (Frontiers in Neurology, 2019)
Eastern equine encephalitis (EEE) is a severe arboviral neuroinvasive disease with high mortality and neurological sequelae. Treatment for EEE is primarily supportive. Intravenous immunoglobulin (IVIg) and high-dose steroids have been used as empirical therapy for EEE with some case reports of benefit. We report a case of a patient who presented with encephalopathy with initial cerebrospinal spinal fluid (CSF) serology analysis showing California serogroup encephalitis virus IgG positivity. However, the rapid clinical deterioration of the patient into a comatose state prompted a second CSF serology analysis that showed seroconversion of high titer Eastern Equine Encephalitis virus IgM and positive titer of California serogroup encephalitis virus IgG. The patient completed a 5-day course of empiric IVIg without concurrent corticosteroid therapy but did not show significant clinical improvement.